Long-term Intervention Effects of Using Smart Bracelets in Community-dwelling Type 2 Diabetes Patients - TAN Ying, CAO Min, CHEN Meiling, ZHAO Zedi, ZHENG Peng, FENG Huiyao, ZHANG Yue, DONG Xiaomei, CHEN Xiongfei, WU Xueji (Zhongguo quanke yixue, 2023)
Background Smart bracelets are increasingly used in chronic disease management, which help improve patient adherence and motivation to exercise interventions, but more evidence for their long-term effectiveness in patients with type 2 diabetes mellitus (T2DM) in the community needs to be explored. Objective To develop an intervention model for community-dwelling type 2 diabetes patients using smart bracelets, and to assess its long-term effectiveness in these patients. Methods From July to August 2018, this study selected 11 community health institutions from 11 districts of Guangzhou (one from each district) as study settings. And from each setting, 10-15 T2DM patients were selected (intervention group), and were compared to sex-matched and age-matched (+/- two years) T2DM patients (control group). The intervention was carried out from September 2018 to August 2019 in two groups, both received standardized health management services provided by the family physician team and underwent the exercise prescribed by an exercise prescriber. The intervention group additionally received health monitoring and management via wearing a smart bracelet, and set personalized exercise challenge goals under the guidance of an exercise prescriber. The score of the Chinese version of Summary of Diabetes Self-Care Activities Measure (SDSCA-C), comprehensive assessment indicators, and attainment rates of key glycemic indicators were compared between the two groups before and after the intervention. Results Ninety-two patients in the control group and 144 patients in the intervention group completed one-year intervention and follow-up. After the intervention, the subscale scores of dietary management and foot care management and the total score of SDSCA-C increased notably in the intervention group (P<0.05), but changed insignificantly in the control group (P>0.05). Two groups had no statistically significant differences in all comprehensive assessment indicators at baseline (P>0.05). After one year of intervention, besides a decrease was found in total cholesterol, apolipoprotein A1 and apolipoprotein B in both groups, a reduction was found in waist circumference in the intervention group, and in fasting plasma glucose (FPG), triacylglycerol and low-density lipoprotein cholesterol in the control group (P<0.05) .In terms of the attainment rate of key indicators, the HbA1c attainment rate increased in the intervention group after intervention (P<0.05), and the post-intervention rate was higher than that of the control group (P<0.05). The FPG attainment rate was higher after intervention in both groups (P<0.05). But the high-density lipoprotein cholesterol attainment rate was lower after intervention in both groups (P<0.05) . Conclusion Using a smart bracelet helps people with T2DM maintain self-management behaviors over time and keep their blood sugar at target levels. As dyslipidemia is an important factor affecting blood glucose control, pharmacological interventions should be initiated as early as possible to regulate lipid metabolism disorders in addition to lifestyle modification.